Techno-economic Analysis of Inclined Solar Dryer for Carrot (Daucus carota L.) Drying - Poonia, Surendra; Singh, A.K.; Jain, Dilip (Annals of Arid Zone, 2022)
Solar dryers’ performance evaluation and economic analysis for drying perishable agricultural produces was undertaken. The dryer was fabricated using locally available materials, e.g., galvanized iron sheet, mild steel angle, glass, and stainless steel wire mesh. The provision of tilting the dryer helps to receive maximum solar radiation round the year thus, captures more solar radiation than that of a horizontal plane. The drying trial for dehydrating carrot (Daucus carota L.) was conducted in this dryer in February 2019. During the performance evaluation, the maximum stagnation temperature inside the drying chamber was observed 68°C, and on loading with 8 kg carrot, it reduced to 58°C, while the outside ambient temperature was 37°C on a clear sky day (from 08:00 h to 18:00 h) in February 2019. During the drying process, the moisture content of the carrot was reduced from 74% (wet basis) to about 13% within three days. The efficiency of the dryer was found to be 17.57%. The economic evaluation of the solar dryer revealed that the high value of IRR (84.4%) and low value of the payback period (1.42 years) make the dryer unit very cost-efficient. The economic indicator cost-benefit ratio was found to be 2.09, which shows the potential of using solar dryers in place of conventional dryers. The economic attributes, namely net present worth (Rs. 41830) and the system’s annuity (Rs. 5635) revealed its economic viability. Inclined solar dryers in remote locations/rural areas can be a useful solar gadget in reducing post-harvest losses and carbon emissions in the arid region of Rajasthan.